Collaborative Science and Digital Tools: Monitoring Heritage at Risk during the People of Guana Project. - Murray, Emily Jane; Miller, Sarah E.; Kemp, Kassie (Journal of Field Archaeology, 2025)
The North American Heritage at Risk (NAHAR) working group developed a research pipeline to employ collaborative methods to address climate impacts at archaeological sites that includes modeling, monitoring, meeting, methodizing, and mitigating. The People of Guana project was the inaugural study using the NAHAR pipeline to focus on a suite of sites located on the Guana Peninsula in northeastern Florida. The project was funded through the National Estuarine Research Reserve System's Science Collaborative (NERRS SC). This paper focuses on collaborative methods employed during monitoring efforts to document eroding resources using the Florida Public Archaeology Network's (FPAN) citizen science program Heritage Monitoring Scouts (HMS Florida). It further focuses on advanced monitoring techniques—shoreline mapping with an Arrow Gold GNSS receiver, terrestrial laser scanning of landscapes, and photogrammetry of exposed artifacts.